The ICAPS Water Mass History File - Fisher, Alvan, Jr (1978)
A new Integrated Command Antisubmarine Warfare Prediction System (ICAPS) data file based on the near-surface water masses of the Northern Hemisphere and the Indian Ocean is discussed. The most attractive feature of the water mass file is that the characteristics of the input bathythermogram will objectively determine the proper deep history for computation of the surface-to-bottom sound speed profile. A second feature is the adjustment of salinity in the presence of temperature inversions (sound channels) to maintain a stable water column. Evaluation of the water mass file using salinity-temperature-depth (STD) data shows that it is improved over the file presently used by ICAPS. The new file is described and the temperature criteria used to define water masses in each area are given. (Author)